2021
DOI: 10.1088/1361-648x/ac28c1
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of non-trivial polar topologies hidden in singular stress field in SrTiO3: topological strain-field engineering

Abstract: Discovery of non-trivial topological structures in condensed matters holds promise in novel technological paradigms. In contrast to ferromagnetics, where a variety of topological structures such as vortex, meron, and skyrmion have been discovered, only few topological structures can exist in ferroelectrics due to the lack of non-collinear interaction like the Dzyaloshinskii-Moriya interaction in ferromagnetics. Here, we demonstrate that polarization structures with a wide range of topological numbers (winding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[26] The different regions including: 1) pure c/a domains, 2) a 1 /a 2 droplets in a c/a matrix, 3) connected-labyrinth structure of c/a domains, 4) broken-labyrinth structure of c/a domains, 5) c/a droplets in an a 1 /a 2 matrix, and 6) pure a 1 /a 2 domains can be identified using this method. This approach provides novel insight into the strain-field tuning of domain structures and ferroelectric topological nanostructures and helps open the door for the new field of "topological strain-field engineering" [62] and "topological defectronics." [63,64] Building from these observations, we focused specifically on the continuous-labyrinth structure which showed local ordering up to a certain finite length and also exhibited the most types of pattern defects in its as-grown state.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The different regions including: 1) pure c/a domains, 2) a 1 /a 2 droplets in a c/a matrix, 3) connected-labyrinth structure of c/a domains, 4) broken-labyrinth structure of c/a domains, 5) c/a droplets in an a 1 /a 2 matrix, and 6) pure a 1 /a 2 domains can be identified using this method. This approach provides novel insight into the strain-field tuning of domain structures and ferroelectric topological nanostructures and helps open the door for the new field of "topological strain-field engineering" [62] and "topological defectronics." [63,64] Building from these observations, we focused specifically on the continuous-labyrinth structure which showed local ordering up to a certain finite length and also exhibited the most types of pattern defects in its as-grown state.…”
Section: Resultsmentioning
confidence: 99%
“…This 2D polarization distribution is also a nontrivial polarization structure that can be characterized by the topological quantity of winding number 1. [ 44 ] Therefore, polar topological phase transitions (i.e., polaron meron‐skyrmion and 2D topology of the polarization field) can also be manipulated by the vertical electric field and mechanical strain.…”
Section: Resultsmentioning
confidence: 99%
“…One of the first theoretical predictions of the topological polar phase was made in the 2000s, where the polar vortex phase was predicted in the low dimensional ferroelectric system (i.e., PZT nanodisks, nanorods, and thin films) via ab initio calculations (Figure 3a). [ 101,102 ] Consequently, other theoretical studies have been reported on the vortex structure, [ 103–125 ] switching dynamics, [ 126–141 ] and properties [ 142–146 ] in various low‐dimensional ferroelectric systems. In particular, in 2006, using phase‐field simulations, J. Wang et al predicted the formation of polar vortex‐like structure in a ferroelectric nanodot (Figure 3b).…”
Section: Topological Polar Structuresmentioning
confidence: 99%